Assessment of accumulation of selected metals by native plants growing in polluted peruvian post-mining areas - Cruzado Tafur, Edith Maricela (2021)
Metal mining is one of the economic pillars of the Peruvian economy. Peru is the main producer of gold, zinc, lead, and tin in Latin America and the second largest producer of copper, silver, and zinc worldwide. Despite its economic importance, mining has also left a plethora of Mining Environmental Liabilities (MEL) whose inadequate waste management represents a risk for both the environment and human health and is a common trigger of social problems. The Cajamarca región is the second región in Peru in terms of the number of MEL sites with the majority of them located in the Hualgayoc district. The goal of the PhD project is the assessment of the environmental impact of MEL in the Peruvian Andes using as an example two post-mining sites in the Hualgayoc district. This evaluation includes the study of soils and native plant species in terms of their metal accumulation potential and the species involved in the process, in order to generate information on a possible use of Andean native plants for phytoremediation. The mineralogical composition of soils is dominated by illite, kaolinite, quartz, and jarosite. Soil analyses also reveals a high acidity, very low content of essential nutrients, and potentially toxic concentrations of Pb, Cd, As, Cu, Ag, and Zn out of the 34 analysed elements. Sequential fractionation soil analyses indicate that the highest content of the metals is in fractions with limitedmetal mobility. Soils are classified as extremely polluted according to several geochemical indexes, thus represent a serious risk to the local ecosystem. The main part of the project concerns native Andean flora and contributes to their inventory with the identification of 22 plants belonging to 12 family species. The metal content in plant organs is correlated with that of the soil, in order to assess the phytoremediation potential of native plant species by establishing their metal bioaccumulation and translocation capabilities. Some plants are found to be potentially suitable for phytoremediation of Cd, Cu, and Zn but none of them for Pb, As, and Ag. The speciation studies carried out by HPLC with parallel elemental (ICP) and molecular (ESI) mass spectrometricdetection allows the identification of the chemical species responsible for the translocation of Cu and Zn. Nicotianamine complexes are the major species of copper and zinc in organs of Arenaria digyna, Nicotiana thyrsiflora and Puya sp.; they are accompanied by deoxymutageneic acid complexes. In addition, a novel, never reported so far, dihydroxy-nicotianamine species was identified as the most abundant Cu and Zn ligand in Hypericum laricifolium.